2011
DOI: 10.1186/1475-2875-10-122
|View full text |Cite
|
Sign up to set email alerts
|

Unexpectedly long incubation period of Plasmodium vivax malaria, in the absence of chemoprophylaxis, in patients diagnosed outside the transmission area in Brazil

Abstract: BackgroundIn 2010, Brazil recorded 3343,599 cases of malaria, with 99.6% of them concentrated in the Amazon region. Plasmodium vivax accounts for 86% of the cases circulating in the country. The extra-Amazonian region, where transmission does not occur, recorded about 566 cases imported from the Amazonian area in Brazil and South America, from Central America, Asia and African countries. Prolonged incubation periods have been described for P. vivax malaria in temperate climates. The diversity in essential biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 16 publications
0
24
0
2
Order By: Relevance
“…This could interfere with malaria detection by passive surveillance systems and can facilitate the onward transmission of malaria. It has been reported that the incubation time for some plasmodium species can last up to four months [18]. Since the majority of the imported malaria cases come from Mozambique where Plasmodium vivax and Plasmodiun malariae, which are known to have longer incubation time, are present [19] there is a possibility that individuals infected with these species may transmit the infection to others even months after their travel.…”
Section: Discussionmentioning
confidence: 99%
“…This could interfere with malaria detection by passive surveillance systems and can facilitate the onward transmission of malaria. It has been reported that the incubation time for some plasmodium species can last up to four months [18]. Since the majority of the imported malaria cases come from Mozambique where Plasmodium vivax and Plasmodiun malariae, which are known to have longer incubation time, are present [19] there is a possibility that individuals infected with these species may transmit the infection to others even months after their travel.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers in Rio de Janeiro and Brasília have recently reported travelers with long incubation periods for malaria, varying from 3 to 12 months after returning from trips to the Amazon. They suggested that temperate strains coexist with the tropical strain in the country 22,27 . This hypothesis is corroborated by the observation of relapses at days 33, 73, 82, 88, 113, 121, and 137 after initiating therapy in a P. vivax malaria treatment cohort in 1990 in Cuiabá (Mato Grosso State), where malaria transmission does not occur 3 .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the 10-year mean minimum temperature in January showed a difference of 7.5℃ [22]. Various explanations have been proposed for the two different incubation periods of P. vivax malaria [23], but the cause is likely not a single factor but rather a complex interaction of environmental factors, such as the meteorological conditions, latitude of risk regions, the principal vector's biological characteristics, adaptation to the environment, and characteristics of the infected cases.…”
Section: Discussionmentioning
confidence: 99%